(untitled) (Fiep Bulletin - online, 2014)
The present work was developed seeking to study "The stress and its relationship with the athletes of Basketball "sporting lesion, using the stress model and sporting lesion of Anderson & Williams, 1988. For the development of this investigation we applied to the team of juvenile Basketball of the youth’s from Caxias do Sul Clube Recreio, a questionnaire based before on the aspects of the model mentioned, Where for the obtained results I was demonstrated that the largest amount of lesions in this team is in those athletes that manifest during the competition negative sensations, as anxiety and discomfort. The researched athletes practice this sport more than ten years the. Introduction: Physical factors as over training and physical fatigue primary causes of the sporting lesions are considered. Even so psychological and social factors can also contribute to the development of lesions (Kerr & Minden, 1988; Anderson & William, 1989; Blackwell & McCullough, 1990; Hardy et., 1991; Petrie, 1993; Lavallee & Flint, 1996; jobson, 1999). Methodology: I was applied the stress Model and sporting lesion (adapted of Anderson & Williams, 1988). Result of the Observation: It was observed that the 60% of the athletes (seven trainings and seven competitions) they manifest behaviors differentiated in the competition in relation to the trainings. Conclusions: With base in the results obtained in the present work, we reached the conclusion that the same athletes that suffer of lesions present negative sensations ( fear) moments before beginning the competition, which can determine restored physiologic exaggerated and to decrease the concentration capacity in the accomplishment of the movement.